2000
DOI: 10.1159/000013585
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammatory Response Syndrome and Acute Renal Failure Associated with <i>Hemophilus influenzae</i> Septic Meningitis

Abstract: Sepsis is often associated with a downward spiral through a spectrum of systemic inflammatory response syndrome (SIRS) culminating in organ failure and death. Here we present a 3-year-old girl with Hemophilus influenzae septic meningitis who developed SIRS and acute renal failure. In the initial stage, the patient showed uremia, cytopenia, disseminated intravascular coagulation, elevation of tissue enzyme and ferritin values, hemophagocytosis and overproduction of nitric oxide. The serum cytokine profile revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Although the advent of vaccination programs has almost eradicated the disease from industrialized countries, this infection is still present in less-developed areas, where it remains the leading cause of childhood meningitis (13). Hib meningitis is associated with increased cerebrospinal fluid levels of proinflammatory cytokines, including tumor necrosis factor alpha (TNF-␣) and interleukin-6 (IL-6), which may have a significant role in the pathophysiology of the disease (5,10,33). TNF-␣ is a key mediator of proinflammatory responses contributing significantly both to host defenses and to the pathophysiology of different infections (4).…”
mentioning
confidence: 99%
“…Although the advent of vaccination programs has almost eradicated the disease from industrialized countries, this infection is still present in less-developed areas, where it remains the leading cause of childhood meningitis (13). Hib meningitis is associated with increased cerebrospinal fluid levels of proinflammatory cytokines, including tumor necrosis factor alpha (TNF-␣) and interleukin-6 (IL-6), which may have a significant role in the pathophysiology of the disease (5,10,33). TNF-␣ is a key mediator of proinflammatory responses contributing significantly both to host defenses and to the pathophysiology of different infections (4).…”
mentioning
confidence: 99%
“…MIS-C is documented to be associated with extremely high plasma levels of proinflammatory cytokines, and consequently very high levels of sIL-2R [19,20]. Similar appears to be true of SIRS of any etiology [21]. This is important because treatment of choice in these conditions significantly differs from that of HLH: the above hyperinflammatory states respond well to intravenous administration of immunoglobulins, with or without IgM enrichment [22].…”
Section: Discussionmentioning
confidence: 91%
“…There are few reports of renal involvement in the hemophagocytic syndrome [43,44]. Acute renal failure following hemophagocytic syndrome is rarely mentioned in the literature [45,46], and renal biopsy is seldom performed. The only reported renal biopsy showed acute tubular necrosis with round cell infiltration and interstitial edema [45].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Nishimura et al [46] recently reported a case of acute renal failure associated with hemophagocytic syndrome associated with Hemophilus influenzae septic meningitis. Systemic inflammatory response syndrome was considered to be responsible for the development of acute renal failure [46,48]. The serum cytokine profile revealed increased levels of inflammatory cytokines, including soluble interleukin (IL)-2 receptor, IL-6, IL-10 and tumor necrosis factor-α [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation